Complexity of fredholm equations of the second kind with kernels from anisotropic classes of differentiable functions - Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish the exact order of complexity of the approximate solution of Fredholm equations with periodic kernels with dominant mixed partial derivative.